Tinjauan Kritis Kewarganegaraan dalam Perspektif Hukum Tata Negara dan Hukum Islam - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Ammar Farid; Jazz Kyanu Azzahra; Siti Hanifah Jauharoh Wahidah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This think around focuses to essentially and comprehensively see at the concept of citizenship from the focuses of see of sacrosanct law and Islamic law. Citizenship may be a legal status that characterizes the rights and commitments of an individual interior a state. Inside the setting of sacrosanct law, citizenship is controlled through constitutions and citizenship laws that incorporate distinctive perspectives such as the benchmarks of citizenship (ius soli, ius sanguinis), human rights, and conscious commitments. Sacrosanct law besides considers the measures of vote based framework, value, and adjust in choosing citizenship status. On the other hand, from the point of see of Islamic law, the concept of citizenship isn't because it were seen from a legal-formal point but in addition incorporates moral and ethical estimations. Islamic law gives heading on the commitments and rights of individuals as parcel of the ummah (the Muslim community), based on Shariah measures such as value ('adl), open welfare (maslahah), and the confirmation of fundamental human rights. Besides, Islamic law considers the rights of non-Muslims interior an Islamic state setting through the concept of